Answer:
t[c(h)] = 700h
Step-by-step explanation:
Got it wrong, and it told me what was right lol
The function is given by:
t[c(h)] = 700h
Step-by-step explanation:Emma burns 350 calories per hour biking.
The function is given by:
c(h) = 350h.
Also, when her little sister tow in the bike then the she burn twice as many calories.
This could be represented by the function:
t(c) = 2c
where c is the number of calories burned per hour.
Now, we are asked to find the function that calculate he number of calories she will burn per hour while biking with her sister in the bike trailer i.e. we are asked to find the composition function:
[tex]t(c(h))[/tex]
Hence, we have:
[tex]t(c(h))=t(350h)\\\\i.e.\\\\t(c(h))=2(350h)\\\\i.e.\\\\t(c(h))=700h[/tex]
the average of 20 numbers is 0. among them at least how many of them can be greater than 0.
a. 19.
b.10
c.0
d.1
Answer:
The correct option is A.
Step-by-step explanation:
The correct option is A.
According to the given statement:
Average of 20 numbers= 0.
So we have avg = sum/20.
That implies sum = 0.
Hence at the most, there can be 19 positive numbers.
(Such that if the sum of these 19 positive numbers is x, 20th number will be -x)....
What can you say about the Y values are the two functions??? Help please !!!!
Answer:
D. The minimum y-value of g(x) approaches -3
Step-by-step explanation:
Form a table for values of x with corresponding values for f(x) and g(x)
x f(x)=3x²-3 g(x)=2^x -3
-3 =3(-3²)-3=24 2⁻³ -3 = -2.88
-2 =3(-2²)-3=9 2⁻² -3 = -2.75
-1 =3(-1²)-3=0 2⁻¹-3 = -2.5
0 =3(0²)-3= -3 2⁰ -3 = -2
1 =3(1²)-3=0 2¹ -3 = -1
2 =3(2²)-3=9 2²- 3 = 1
3 =3(3²)-3=24 2³ -3= 5
From the table above, you can see the minimum value of y in g(x) -2.88 approaches -3
What is the measure of the angle of intersection when AB is the
perpendicular bisector of XY?
ОА. 60°
ов. 45°
Ос. 30°
Op. 90°
Answer:
Option 90°
Step-by-step explanation:
AB is the perpendicular bisector of XY
The result of intersection will give 4 right angles
So,the measure of the angle of intersection when AB is the perpendicular bisector of XY = 90°
See the attached figure.
Which term is a perfect square of the root 3x^4
Answer:
The perfect square of 3*4 is 9*16
Step-by-step explanation:
A perfect square is a number that can be expressed as the product of two equal integers.
For example 64 is a perfect square because if we multiply 8 two times we will get 64.
Thus the given expression is 3 * 4.
To find perfect square we square the numbers:
3² = 3*3 = 9
4² = 4*4 = 16
Thus the perfect square of 3*4 is 9*16 ....
Answer:
[tex]9x^8[/tex]
Step-by-step explanation:
We need to find perfect square of the root [tex]3x^{4}[/tex]
To find the perfect square, we need to square the root [tex]3x^{4}[/tex]
[tex](3x^{4})^2[/tex]
Now let's use exponent power rule and simplify.
[tex](a^{m})^n = a^{mn}[/tex]
= [tex]3^2x^{4*2} = 9x^8[/tex]
Therefore, [tex]9x^8[/tex] is perfect square of the root [tex]3x^4.[/tex]
Nigel, Gina, and Kamal each spend between $15 and $20 on dog supplies.
Nigel bought 4 items.
Gina bought 5 items.
Kamal bought 2 items.
The prices of the items are given below. Drag items to each box to show what each person could have bought.
Answer:
456+56+54+4+4
Step-by-step explanation:
65+465+5+56
sorry, for the 4 items i got it wrong.
5 items: 1 dog bone, 3 water bowls, 1 collar
2 items: 1 box of dog food, 1 collar
The given line passes through the points (0, -3) and (2, 3).
What is the equation, in point-slope form of the line that is
parallel to the given line and passes through the point (
-1, -1)?
Answer:
y - 1 = (1/3)(x + 1)
Step-by-step explanation:
Look carefully at (0, -3) and (2, 3). As we move from the first to the second, x increases by 2 (from 0 to 2) and y increases by 6 (from -3 to 3). Therefore, the slope of this line is m = rise / run, or m = 6/2, or m = 1/3. Both lines have the same slope, 1/3, because they are parallel.
Now let's apply the point-slope form of the equation of a straight line. Here the point in question is (-1, 1) and the slope is 1/3. Therefore, we have:
y - 1 = (1/3)(x + 1)
Answer:
Step-by-step explanation:
The table gives the populations of three countries in 2013.
United States
3.16 x 108
Brazil Germany
1.96 * 108 8.0 x 107
Arrange the sums and differences in increasing order of their values.
the difference of
the populations
of Germany and
Brazil
the sum of the
populations of
the United States
and Brazil
the difference of
the populations
of Brazil and the
United States
the sum of the
populations of
Brazil and
Germany
Answer:
Arranging the sum and differences in increasing order of their values.
1) Difference of the populations of Germany and Brazil = 1.16 X 10^8
2) Difference of the populations of Brazil and the United States = 1.2 X 10^8
3) Sum of the populations of Brazil and Germany = 2.76 X 10^8
4) Sum of the populations of the United States and Brazil = 5.12 X 10^8
Step-by-step explanation:
Population of United States: 3.16 X 10^8
Population of Brazil : 1.96 X 10^8
Population of Germany: 8 X 10^7
a) the difference of the populations of Germany and Brazil
Difference of the populations of Germany and Brazil = 1.96 X 10^8 - 8 X 10^7 = 116000000 = 1.16 X 10^8
b) the sum of the populations of the United States and Brazil
Sum of the populations of the United States and Brazil = 3.16 X 10^8 + 1.96 X 10^8 = 512000000 = 5.12 X 10^8
c) the difference of the populations of Brazil and the United States
Difference of the populations of Brazil and the United States = 3.16 X 10^8 - 1.96 X 10^8 = 120000000 = 1.2 X 10^8
d) the sum of the populations of Brazil and Germany
Sum of the populations of Brazil and Germany: 1.96 X 10^8 + 8 X 10^7 = 276000000 = 2.76 X 10^8
Arranging the sum and differences in increasing order of their values.
1) Difference of the populations of Germany and Brazil = 1.16 X 10^8
2) Difference of the populations of Brazil and the United States = 1.2 X 10^8
3) Sum of the populations of Brazil and Germany = 2.76 X 10^8
4) Sum of the populations of the United States and Brazil = 5.12 X 10^8
sum of first nth term of the seris 2^2+4^2+6^2+8^2+.........n terms is
Answer:
(2/3)n(n+1)(2n+1)
Step-by-step explanation:
First you have to find the general term formula which is here (2k)^2 which is equal to 4k^2. Sum(k=1 to n) of 4k^2=4•n(n+1)(2n+1)/6
simplified to (2/3)n(n+1)(2n+1)
Julio is visiting Bridal Veil Falls in Telluride Colorado. From the top of the 365 foot waterfall he looks down at an angle of depression of 27° and spots a bear fishing in the stream. To the nearest foot, how far is the bear from the base of the waterfall?
To find the distance from the bear to the base of the waterfall, we can use the tangent function, which relates the angle of depression to the distance. Using the given angle of depression of 27° and height of 365 feet, we can calculate that the bear is approximately 632 feet from the base of the waterfall.
Explanation:To find the distance from the bear to the base of the waterfall, we can use the tangent function, which relates the angle of depression to the distance.
In this case, we have an angle of depression of 27° and a height of 365 feet.
Let's denote the distance we're trying to find as x.
The tangent of the angle of depression is equal to the opposite side (365 feet) divided by the adjacent side (x).
So we can set up the equation tan(27°) = 365/x and solve for x.
Rearranging the equation, we have x = 365/tan(27°). Plugging in the values and using a calculator, we find that x is approximately 632 feet.
The bear is approximately 717 feet away from the base of the waterfall.
To find out how far the bear is from the base of the waterfall, use trigonometry, specifically the tangent of the angle of depression. Tangent relates the opposite side and the adjacent side in a right triangle.
1. Given Information:
- Height of the waterfall (opposite side), h = 365 feet.
- Angle of depression, [tex]\( \theta = 27\textdegree[/tex].
2. Formulate the Tangent Function:
The tangent of an angle in a right triangle is given by [tex]\( \tan(\theta) = \frac{\text{opposite}}{\text{adjacent}} \)[/tex].
So in our case, [tex]\( \tan(27\textdegree) = \frac{365}{d} \)[/tex].
3. Solving for d (the distance from the base of the waterfall to the bear):
Rearranging for d:
[tex]\[ d = \frac{365}{\tan(27\textdegree)} \][/tex]
4. Calculate the Value:
Using a calculator to find [tex]tan(27\textdegree)[/tex] which is approximately 0.5095.
[tex]\[ d = \frac{365}{0.5095} \approx 716.5 \text{ feet} \][/tex]
5. Round to the Nearest Foot:
[tex]\[ d \approx 717 \text{ feet} \][/tex]
So, the distance between the bear and base of the waterfall is approximately 717 feet.
If f(x)=5x3 and g(x) = 2x+1 find (f+g)(x). Help please
Answer:
5x^3 +2x -1
Step-by-step explanation:
f(x)=5x^3-2 and g(x) = 2x+1
(f+g)(x) = 5x^3-2 + 2x+1
Combine like terms
= 5x^3 +2x -1
The diagram below shows a square inside a regular octagon. The apothem is of the octagon is 13.28 units. To the nearest square unit, what is the area of the shaded region?
Answer:
I found the image of this problem. Its side measure is 13. The octagon can form 8 triangles. Its apothem can serve as the height of the triangle. We need to get the area of the triangle and multiply it by 8. We then deduct the area of the square from the total area.
Area of a triangle = (height * base) / 2
A = (15.69 * 13) / 2
A = 203.97 / 2
A = 101.985 sq. units
101.985 x 8 = 815.88 sq. units
Area of the square = s²
A = 13²
A = 169 sq. unit
Area of the shaded region: 815.88 sq. unit - 169 sq. unit = 646.88 sq. unit
Step-by-step explanation:
A little help on this math problem?
If you know Heron's formula, this is easy.
[tex]\text{area}=\sqrt{s(s-6)(s-10)(s-14)}=15\sqrt3[/tex]
where [tex]s=\dfrac{6+10+14}2=15[/tex] is the semiperimeter of the triangle.
The area is also equal to half the product of the base and height of the triangle, which happen to be
[tex]15\sqrt3=\dfrac{14x}2\implies x=\dfrac{15\sqrt3}7\approx3.711[/tex]
so the answer is B.
What is the solution to the system of equations below?
(9, –36)
(9, 0)
(–9, 18)
(–9, –42)
Answer:
x = 9, y = -36 → (9, -36)Step-by-step explanation:
[tex]y=-3x-9\qquad(1)\\\\y=\dfrac{1}{3}x-39\qquad(2)\\\\\text{Substitute (1) to (2)}\\\\-3x-9=\dfrac{1}{3}x-39\qquad\text{multiply both sides by 3}\\\\-9x-27=x-117\qquad\text{add 27 to both sides}\\\\-9x=x-90\qquad\text{subtract}\ x\ \text{from both sides}\\\\-10x=-90\qquad\text{divide both sides by (-10)}\\\\x=9[/tex]
[tex]\text{Put the value of x to (1):}\\\\y=-3(9)-9\\\\y=-27-9\\\\y=-36[/tex]
Answer:
It is A
Step-by-step explanation:
Solve Ax + By = −C for x.
The value of x from the given algebraic expression Ax + By = −C would be x = (-C - By)/ A.
What is a linear equation?A linear equation is an equation that has the variable of the highest power of 1. The standard form of a linear equation is of the form Ax + B = 0.
In order to solve x, if we isolate the x variable from the rest of the other variables.
Given algebric expression;
Ax + By = -C
1. Subtract By from the right side
Ax + By -By = -C -By
Ax = -C - By
2. Divide A
x = (-C - By)/ A
Hence, The value of x from the given algebraic expression Ax + By = −C would be x = (-C - By)/ A.
Learn more about linear equations;
https://brainly.com/question/10413253
#SPJ5
if you reflect ΔFGH across the x-axis, what will be the coordinates of the vertices of the image ΔF'G'H
Answer:
A
Step-by-step explanation:
Under a reflection in the x- axis
a point (x, y ) → (x, - y )
Hence
F(- 2, - 1 ) → F'(- 2, 1 )
G(2, 2 ) → G'( 2, - 2 )
H(4, - 3 ) → H'(4, 3 )
negitive 7 over 18 minus negitive 9 over 4 equals?
Answer:
1 31/36 is your answer
Step-by-step explanation:
Find common denominators. Note that what you do to the denominator, you must do to the numerator;
(-7/18)(2/2) = (-14/36)
(-9/4)(9/9) = (-81/36)
Combine the terms:
(-14/36) - (-81/36)
Note that two negative signs directly next to each other equals a positive sign.
(-14/36) + 81/36
-14/36 + 81/36
(-14 + 81)/36
Combine like terms. Solve the parenthesis:
(67)/36
Change to a mixed fraction:
(67/36) = 1 31/36
1 31/36 is your answer.
~
what's the sum of a number k and 7
what is the y intercept of the line given by the equation below? y=4x-3
Answer:
y-intercept of y=4x-3 is -3
Step-by-step explanation:
The given equation is:
y = 4x -3
The equation is in slope-intercept form.
The standard equation of slope-intercept form is:
y = mx + b
where m is the slope and b is the y-intercept
So, comparing the given equation with the standard equation the y-intercept is -3
y-intercept of y=4x-3 is -3
Answer:
Step-by-step explanation:
The y intercept of any equation that is a function is the y value taken on when x = 0
So in this case it is y = - 3 because 4*0 = 0. All that is left for y is y = -3.
The point of interception is (0.-3). The way to confirm many answers is to graph the point.
Quadrilateral UVWX is reflected over the x-axis to form quadrilateral U′V′W′X′.
If vertex U is located at (-4, 5) and vertex V is located at (-6, 2), then vertex U′ is located at blank and vertex V′ is located at blank
Answer:
U' = (-4,-5)
V' = (-6,-2)
Step-by-step explanation:
Vertex U has coordinates
U = (-4,5)
Vertex V has coordinates
V = (-6,2)
When a quadrilateral is reflected across x- axis the sign of x coordinate remains same and sign of y coordinate changes.
So, U= (-4,5)
then U' is:
U' = (-4,-5)
V = (-6,2)
then V' is
V' = (-6,-2)
Answer:
(-4, -5) and V' is at (-6, -2)
Do you guys the answer for number 3
Answer:
17(21) - 14(20) = 357 - 280 = 77 ft²
The correct answer is I.
a walking path across a park is represented by the equation y=-2x-7. A new path will be built perpendicular to this path.The paths will intersect at the point (-2,-3).Identify the equation that represents the new path.
Answer:
The equation that represents the new path is y=(1/2)x-2
Step-by-step explanation:
step 1
Find the slope of the give line
we have
y=-2x-7
so
the slope m is equal to
m=-2
step 2
Find the slope of the perpendicular line to the given line
Remember that
If two lines are perpendicular, then their slopes are opposite reciprocal of each other
so
we have
m=-2 -----> slope of the given line
therefore
The slope of the perpendicular line is equal to
m=1/2
step 3
With m=1/2 and the point (-2,-3) find the equation of the line
y-y1=m(x-x1)
substitute
y+3=(1/2)(x+2)
y=(1/2)x+1-3
y=(1/2)x-2 -----> equation that represent the new path
Answer:
Y= 1/2x-2
Step-by-step explanation:
Apex
Hope this helps Have a nice day
evaluate (root5+root2)^2+(root8-root5)^2
Answer
2(10 - √10) or 13.68 to the nearest hundredth.
Step-by-step explanation:
(√5 + √2)^2 + (√8 - √5)^2
= 5 + 2 + 2√5√2 + (8 + 5 - 2√8√5)
= 7 + 2√10 + 13 - 2√40
= 20 + 2√10 - 2√40
= 20 + 2√10 - 4√10
= 20 - 2√10
= 2(10 - √10).
which number is prime ?
A : 8
B : 6
C : 13
D : 10
C : 13
8 is not a prime number since it's dividable by multiple numbers. For example 2(4), 1(8)
6 is not a prime number since it's dividable by 3(2), 1(6)
13 is a prime number because it's only dividable by itself.
10 is not a prime number because it can be divided by 5(2), 1(10)
So only 13 matches as a prime number.
Use the information given in the diagram. Tell why UX=VW and UVW=WXU (51)
its given if already with all the dashes and circle thingys so it's A I'm quite sure
Reflexive property and transitive property.
The answer is option D.
What is Reflexive property?In algebra, the reflexive assets of equality state that a number is continually the same as itself. Reflexive belongings of equality. If a is various, then. a = a.
What is transitive property?In math, if A=B and B=C, then A=C. So, if A=5 for instance, then B and C should both also be five with the aid of the transitive property. That is actually—a foundational property of—math because numbers are constant and both facets of the equals signal need to be equal, by definition.
Learn more about the transitive property here: brainly.com/question/1601404
#SPJ2
Consider the function represented by 9x + 3y = 12 with x as the independent variable. How can this function be written
using function notation?
f(x)=
x+4
Mark this and return
Save and Exit
Next
Submit
Answer:
f(x)=-3x+4
Step-by-step explanation:
We need to solve for y.
9x+3y=12
Subtract 9x on both sides.
3y=-9x+12
Divided both sides by 3.
y=-3x+4
Replace y with f(x).
f(x)=-3x+4
Answer:
[tex]f(x)=-3x+4[/tex]
Step-by-step explanation:
the function represented by [tex]9x + 3y = 12[/tex]
To write the given equation in f(x), we need to solve for y
Lets solve the given equation for y
[tex]9x + 3y = 12[/tex]
Subtract 9x from both sides
[tex]3y =-9x+12[/tex]
Now divide whole equation by 3, divide each term by 3
[tex]y =-3x+4[/tex]
To write it as a function , finally we replace y with f(x)
[tex]f(x)=-3x+4[/tex]
Which product is equivalent to 25x2 – 16?
(5x − 4)(5x + 4)
(5x + 8)(5x − 8)
(5x − 4)(5x − 4)
(5x − 8)(5x − 8)
Answer:
(5x - 4)(5x + 4)Step-by-step explanation:
[tex]25x^2-16=5^2x^2-4^2=(5x)^2-4^2\\\\\text{use}\ a^2-b^2=(a-b)(a+b)\\\\=(5x-4)(5x+4)[/tex]
The correct product which is equivalent to 25x² - 16 is,
⇒ (5x + 4) (5x - 4)
What is Multiplication?To multiply means to add a number to itself a particular number of times. Multiplication can be viewed as a process of repeated addition.
Given that;
The expression is,
⇒ 25x² - 16
Now, We can simplify as;
⇒ 25x² - 16
⇒ (5x)² - 4²
⇒ (5x + 4) (5x - 4)
Thus, The correct product which is equivalent to 25x² - 16 is,
⇒ (5x + 4) (5x - 4)
Learn more about the multiplication visit:
https://brainly.com/question/10873737
#SPJ7
Solve the equation. 9+ m/5 =19
Answer:
m = 50
Step-by-step explanation:
Simplify:
9 + m/5 = 19
9 + 1/5m = 19
1/5m + 9 = 19
Subtract 9 from both sides:
1/5m + 9 - 9 = 19 - 9
1/5m = 10
Multiply both sides by 5:
5 ⋅ ( 1/5m ) = ( 5 ) ⋅ (10)
Therefore m = 50What is the solution to the system
Answer:
hello : (5,2,2)
Step-by-step explanation:
put x = 5 in this equation : y=3(5)-13=15-13=2
put x= 5 and y=2 and z=2 in the first and second equation you have -3(5)+4(2)+2(2)=-3 -15+8+4 =-3 so :-3=-3 .....right
2(5)-4(2)-2 =0 10-8-2=0 so : 0=0 .....right
Find the measure of ∠ECB.
a) 25
b) 96
c) 118
d) 146
Answer:
Option A. ∠ECB=25°
Step-by-step explanation:
we know that
The measurement of the outer angle is the semi-difference of the arcs it encompasses.
so
∠ECB=(1/2)[arc DB-arc EB]
substitute the given values
(x+10)°=(1/2)[146°-(6x+6)°]
solve for x
2x+20=140-6x
2x+6x=140-20
8x=120
x=15
Find the measure of angle ECB
∠ECB=x+10=15+10=25°
Answer:
25
Step-by-step explanation:
I really need help with number 55
Answer:
see below
Step-by-step explanation:
Take the 4 lb container. Pour out rice and fill the 3 lbs container. What is left in the 4 lb container is 1 lb (4-3 =1)
Empty the 3 lbs container and put the 1lbs into it
Now measure rice into the 4 lbs container
We have 1lbs ( in the 3lbs container)
and 4 lbs ( in the 4 lbs container)
for a total of 5 bs